Rictor maintains endothelial integrity under shear stress - Li, Hui; Zhou, Wen-Ying; Liu, Yi-Xian; Xia, Yi-Yuan; Xia, Chun-Lei; Pan, Dao-Rong; Li, Zheng; Shi, Yi; Chen, Shao-Liang; Zhang, Jun-Xia (Frontiers in Cell and Developmental Biology, 2022)
Background: Endothelial injury induced by low shear stress (LSS) is an initiating factor in the pathogenesis of various cardiovascular diseases, including atherosclerosis, hypertension, and thrombotic diseases. Low shear stress activates the mammalian target of rapamycin complex 2 (mTORC2) signaling pathway. Rictor, the main constituent protein of mTORC2, is involved in vascular development. However, the impact of conditional Rictor ablation on endothelial homeostasis, especially on endothelial-specific markers, such as vascular endothelial-cadherin (VE-cadherin) and von Willebrand factor (VWF), under blood flow stimulation is unclear. Objective: We aimed to investigate whether endothelial Rictor is involved in maintaining vascular endothelial integrity and the potential role of Rictor in atheroprone blood flow-mediated endothelial injury. Methods and results: Immunofluorescence staining showed that endothelial Rictor was successfully knocked out in a mouse model. Scanning electron microscopy (EM) detection revealed disruption of the endothelial monolayer in the thoracic aorta of Rictor-deficient mice. Furthermore, scanning electron microscopy and transmission electron microscopy showed that Rictor deletion disrupted endothelial integrity and expanded cell junctions in the left common carotid artery region. In vitro, low shear stress disrupted actin filament polarity and the promoted the translocation of vascular endothelial-cadherin, the key component of adherens junctions (AJs) in human umbilical vein endothelial cells. After Rictor downregulation by small interfering RNA, the translocation of vascular endothelial-cadherin and stress fibers increased. Rictor knockdown inhibited low shear stress-induced von Willebrand factor upregulation, and downregulation of vascular endothelial-cadherin decreased low shear stress-induced von Willebrand factor expression. These results suggest that vascular endothelial-cadherin/von Willebrand factor is a possible mechanism mediated by Rictor in the pathological process of low shear stress-induced endothelial injury. Conclusion: Rictor is a key protein that regulates endothelial integrity under vascular physiological homeostasis, and Rictor mediates low shear stress-induced endothelial injury by regulating adherens junctions and von Willebrand factor.